Hubungan Asupan Energi, Aktivitas Fisik, dan Kualitas Tidur dengan Kejadian Obesitas pada Mahasiswa Program Studi Kimia Universitas Negeri Surabaya - Isna Khoiril Hidayah; Satwika Arya Pratama (Jurnal Sains dan Kesehatan, 2026)
Obesity is a nutritional problem that remains a global concern, including in Indonesia, where it is on the rise among young adults. This condition results from an energy imbalance, low physical activity, and poor sleep quality. This study aims to analyze the relationship between energy intake, physical activity, and sleep quality with the incidence of obesity among students in the Chemistry Study Program at Surabaya State University. This study employed a cross-sectional design with a sample size of 61 students selected using simple random sampling. Data were collected directly using the Semi-Quantitative Food Frequency Questionnaire (SQFFQ), the Global Physical Activity Questionnaire (GPAQ), the Pittsburgh Sleep Quality Index (PSQI), and anthropometric measurements, were then analyzed using the chi-square test and Fisher's exact test. The results showed that the majority of students had insufficient energy intake (70.5%), moderate physical activity (45.9%), poor sleep quality (72.1%), and were classified as non-obese (75.4%). Meanwhile, students with insufficient energy intake (54.1%), moderate physical activity (41.0%), and poor sleep quality (47.5%) were classified as non-obese. The results of the statistical tests indicated that there was no association between energy intake and the incidence of obesity (p=0.470), there was an association between physical activity and the incidence of obesity (p=0.024), and there was an association between sleep quality and the incidence of obesity (p=0.006).